2010
DOI: 10.1073/pnas.1012236107
|View full text |Cite
|
Sign up to set email alerts
|

RNA-mediated epigenetic regulation of DNA copy number

Abstract: Increasing evidence suggests that parentally supplied RNA plays crucial roles during eukaryotic development. This epigenetic contribution may regulate gene expression from the earliest stages. Although present in a variety of eukaryotes, maternally inherited characters are especially prominent in ciliated protozoa, in which parental noncoding RNA molecules instruct whole-genome reorganization. This includes removal of nearly all noncoding DNA and sorting the remaining fragments, producing extremely gene-rich s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
64
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 41 publications
2
64
1
Order By: Relevance
“…The long macronuclear RNAs in Oxytricha have an additional surprising function in epigenetic genome regulation: These RNAs regulate not only the genome rearrangements, but also the chromosome copy numbers in the macronuclear development (Nowacki et al 2010). In the macronucleus, chromosomes of the diploid zygotic nucleus are amplified by endoreplication.…”
Section: Dna Unscrambling Is Templated By Maternal Rnasmentioning
confidence: 99%
“…The long macronuclear RNAs in Oxytricha have an additional surprising function in epigenetic genome regulation: These RNAs regulate not only the genome rearrangements, but also the chromosome copy numbers in the macronuclear development (Nowacki et al 2010). In the macronucleus, chromosomes of the diploid zygotic nucleus are amplified by endoreplication.…”
Section: Dna Unscrambling Is Templated By Maternal Rnasmentioning
confidence: 99%
“…On the basis of sequence, the telomere-to-telomere RNA transcripts of MAC chromosomes may perform myriad roles during post-zygotic development. For example, the lncRNAs not only guide DNA rearrangement, but also establish DNA dosage levels (Nowacki et al 2010) and provide the possible precursors to piRNAs that protect regions of the germline DNA from elimination (Fang et al 2012;Zahler et al 2012). The present study identified template RNAs for both scrambled and nonscrambled loci, as well as for "IES-less" chromosomes that require no DNA deletion and only excision from the MIC genome plus telomere addition.…”
Section: Discussionmentioning
confidence: 99%
“…During the sexual phase of the life cycle, genome-wide transcription of the somatic chromosomes from the parental macronucleus produces long noncoding template RNAs that guide DNA rearrangements (Nowacki et al 2008;Khurana et al 2014;Lindblad et al 2017) and also regulate chromosome copy number in the progeny (Nowacki et al 2010); however, the mechanism is unclear. The new class of sRNAs reported in this manuscript could derive from these Small RNAs and DNA copy-number regulation www.rnajournal.org 25 maternal template RNAs that appear post fertilization.…”
Section: Discussionmentioning
confidence: 99%
“…Either the cells with the strongest phenotype are depleted from the asexually growing population, consistent with the increased death rate among the mutants, or alternatively, the paralogs of genes under study may act redundantly in the DNA dosage pathway, thus ameliorating the effects we report here. On the other hand, the conjugation-specific lncRNAs (Nowacki et al 2010) are potential substrates for these sRNAs, and their amplification could lead to a stronger downstream effect on the target DNA copy number.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation